IL-17 and CCR9+α4β7– Th17 Cells Promote Salivary Gland Inflammation, Dysfunction, and Cell Death in Sjögren’s Syndrome - Hwang, Sun-Hee; Woo, Jin Seok; Moon, Jeonghyeon; Yang, SeungCheon; Park, Jin-Sil; Lee, JaeSeon; Choi, JeongWon; Lee, Kun Hee; Kwok, Seung-Ki; Park, Sung-Hwan; Cho, Mi-La (Frontiers in Immunology, 2021)
Previous studies have evaluated the roles of T and B cells in the pathogenesis of Sjögren’s syndrome (SS); however, their relationships with age-dependent and metabolic abnormalities remain unclear. We examined the impacts of changes associated with aging or metabolic abnormalities on populations of T and B cells and SS disease severity. We detected increased populations of IL-17-producing T and B cells, which regulate inflammation, in the salivary glands of NOD/ShiLtJ mice. Inflammation-induced human submandibular gland cell death, determined based on p-MLKL and RIPK3 expression levels, was significantly increased by IL-17 treatment. Among IL-17-expressing cells in the salivary gland, peripheral blood, and spleen, the α4β7 (gut-homing integrin)-negative population was significantly increased in aged NOD/ShiLtJ mice. The α4β7-positive population markedly increased in the intestines of aged NOD/ShiLtJ mice following RA treatment. A significant increase in α4β7-negative IL-17-expressing cells in salivary glands may be involved in the onset and progression of SS. These results suggest the potential therapeutic utility of RA in SS treatment.